Studi Layanan Bimbingan Dan Konseling Oleh Guru Dalam Mengatasi Kesulitan Belajar Siswa Di Sekolah Dasar Muhammadiyah 22 Sruni Tahun 2016/2017 - Rahmawati, Eva; , Honest Ummi Kaltsum, S.S., M.Hum (2017)
The purpose of this research is to know: (1) guidance and counseling services, (2) knowing students learning difficulties, (3) describes the difficulties of teachers in the implementation of guidance and counseling in primary school Muhammadiyah Sruni 22 and (4) solutions to overcome teacher difficulties. This research uses qualitative descriptive study type, design research with Phenomenology. Data collection techniques used interviews, observation and documentation, source data from students, teachers and the principal. The validity of the data using triangulation techniques and triangulation of sources. Data analysis techniques using interactive models, Miles and Huberman, namely the reduction of data, data presentation, data verification. The results showed that (1) the implementation of guidance and counseling in primary school Muhammadiyah 22 Sruni executed by master class by using the Special guidance book and carry out a service orientation, information services, placement and distribution service, service learning, individual counseling services, tutoring service group, (2) learning difficulties faced by students in the form of difficult in understanding reading and math, learning difficulties of students can be seen from the value of students under the student's attitude and the KKM is lacking passion , seeking attention and interfere with friends, the solution by using the techniques of individual guidance, technical guidance and remedial groups, (3) such teacher difficulties faced in terms of time, (4) the solution to maximize time at school by providing additional hours after school and provide guidance when learning.